2002
DOI: 10.1080/08910600260081784
|View full text |Cite
|
Sign up to set email alerts
|

Association between Tonsillar Core Microflora and Post-tonsillectomy Bacteremia

Abstract: The aim of the study was to determine whether the population levels of aerobic and anaerobic bacteria in the core tonsils of adults with recurrent acute tonsillitis in uence the developmen t of post-tonsillectomy bacteremia. F or that purpose we performed qualitative and quantitative bacteriology of 24 excised tonsillar core specimens, together with aerobic and anaerobic perioperative blood cultures. The blood cultures from ten non-surgica l patients with recurrent acute tonsillitis served as controls to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…The bacteriological culture was performed according to the previously described method [18]. Briefly, after excision, one of the tonsils was placed in a sterile Petri dish and taken immediately to the microbiology laboratory.…”
Section: Methodsmentioning
confidence: 99%
“…The bacteriological culture was performed according to the previously described method [18]. Briefly, after excision, one of the tonsils was placed in a sterile Petri dish and taken immediately to the microbiology laboratory.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have found an abundance of potentially pathogenic bacteria in recurrently inflamed palatine tonsils (8–11); however, many others have described normal flora (12–14). In our previous study, no correlation was found between the bacterial population levels in the tonsillar microflora and the development of post‐tonsillectomy bacteremia (5).…”
mentioning
confidence: 90%
“…The occurrence of post-tonsillectomy bacteremia is a well-recognised phenomenon, with reported incidences of 20-40% in children and adults (2)(3)(4)(5). The process where viable bacteria penetrate mucosal surfaces to reach the bloodstream and other normally sterile body sites has been defined as bacterial translocation (6).…”
mentioning
confidence: 99%
“…10 Many distinct kinds of microorganisms were detected in the tonsil core as opposed to the tonsil surface in the culture results recovered from the tonsillar surface swabs and tonsillar core tissue, particularly anaerobic bacteria. 14,15,16 The Mc Isaac Modified Centor criteria were the most recent parameters utilized to determine the etiology of tonsillitis. This score is primarily used to identify tonsillitis produced by the GABHS virus and to assist distinguish between tonsillitis caused by bacteria or viruses.…”
Section: Introductionmentioning
confidence: 99%